Manifestaciones en la Cavidad Oral en Pacientes con Tratamiento de quimioterapia en el Hospital Universitario Hernando Moncaleano Perdomo de la Ciudad de Neiva del 30 de octubre de 2019 al 18 de febrero de 2020 (2020)
Cancer is a pathology that has killed more than 8.2 million in 2012 worldwide, its treatment is one of the most aggressive, where chemotherapy stands out, it is a treatment with drugs to interrupt the formation of cancer cells, either through its destruction or by preventing its multiplication. In Colombia, around 33 thousand people die with this diagnosis per year, in addition to 93.02 cases per 100,000 inhabitants, where the one with the greatest tendency is stomach cancer; The prevalence of these diseases in the department of Huila is above the national level, with a prevalence of 19.18 per 100,000 inhabitants, with the national prevalence being 11.36 per 100,000 inhabitants. During these treatments, people tend to undergo changes in the cavity, but these changes are little taken into account and have not been analyzed, since oral health has lagged behind the multiple disciplines that can be brought together; such as the prevalence of oral health disorders as part of the side effects of such treatment. In this study, alterations such as inflammation and increased coloration of the gums, among others